2011
DOI: 10.1590/s0100-06832011000600035
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and soil properties in restoration areas in the jequitinhonha valley, Minas Gerais

Abstract: ABSTRACTrestoration areas, in general, did not differ from the control: eucalypt plantation and Cerrado either. Compared to the forest, the levels of organic C, microbial C, basal respiration (Rbasal) and hydrolysis of fluorescein diacetate (FDA) in the restoration areas were, in general, lower and did not differ in qCO 2 and microbial quotient (qMIC). In general, the soil quality was similar in the initial and advanced restoration stages. Most of the soil and microbial properties in the three years indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Other studies have shown that the hydrolysis of FDA is an effective indicator of the soil quality in degraded areas in restoration processes [19,20] due to the fact that FDA assays and soil respiration are biochemical standards that change rapidly and show sensitivity to stress and soil reclamation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that the hydrolysis of FDA is an effective indicator of the soil quality in degraded areas in restoration processes [19,20] due to the fact that FDA assays and soil respiration are biochemical standards that change rapidly and show sensitivity to stress and soil reclamation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Foi calculada a relação entre C microbiano e C total (Cmic/Ctquociente microbiano), e a partir da razão entre a respiração edáfica e o carbono da biomassa microbiana, obteve-se o quociente metabólico (qCO2). Esses dois parâmetros auxiliam a melhor compreensão da dinâmica da matéria orgânica do solo (Santos et al, 2011).…”
Section: Amostragem De Solo Para Análises Microbiológicas Do Solounclassified